1989
DOI: 10.1159/000120480
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dysphagia, Vomiting and Gastroesophageal Reflux as Manifestations of a Brain Stem Glioma: A Case Report

Abstract: Brain stem glioma is the third most common childhood brain tumor, comprising 10–15% of this group of neoplasms. Typical presenting symptoms include ataxia, diplopia and headache, while signs of increased intracranial pressure occur later in the clinical course. Although prolonged failure to thrive, characterized by cachexia and vomiting are rare manifestations of brain stem lesions, in this study we report a 9.5-year-old boy with failure to thrive since infancy which remitted after excision of a brain stem ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several case studies have reported dysphagia as a primary or secondary complaint in patients with [6][7][8]. Mukand et al [9] conducted a study investigating the common neurologic problems in adults with brain tumors admitted for inpatient rehabilitation.…”
mentioning
confidence: 99%
“…Several case studies have reported dysphagia as a primary or secondary complaint in patients with [6][7][8]. Mukand et al [9] conducted a study investigating the common neurologic problems in adults with brain tumors admitted for inpatient rehabilitation.…”
mentioning
confidence: 99%
“…We tentatively diagnosed this patient with atypical Möbius syndrome ( Table 1), based on these considerations. The association of GERD and brainstem dysfunction in the present patients may be reminiscent of some cases with brainstem glioma [8,15,32], where GER was the initial manifestation of the dysfunction of the medulla oblongata.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, the dysfunction of vago-vagal reflex through the medullary tegmentum can be regarded as an important factor, if not the sole factor, of dysphagia and GERD. These complications can be the initial or predominating symptom of brainstem lesions in patients with glioma [8,15,23] or Chiari malformations [23], similar to patient 4. We propose the term "dysphagia-GER complex" to describe the disturbed motility of the upper digestive tract due to brainstem dysfunction, particularly involving the NTSmediated reflex pathways.…”
Section: Discussionmentioning
confidence: 80%
“…For this reason, unless specifically mentioned, cases published before 1950 are omitted in this discussion, as is 1 associated with osteopenia.24 More recent reports of weight loss associated with these tumors indicate that weight loss can be severe early in the disease. [1][2][3][4][5][6]9,10,[12][13][14][15][16]19 The second case of Burr et a12 is included even though tumor probably extended around the third ventricle because there was good weight and height gain after excision of the brain stem tumor.…”
Section: Discussionmentioning
confidence: 99%